Sediment type and the clonal size greatly affect the asexual reproduction, productivity, and nutrient absorption of Vallisneria natans. Issue 2 (22nd December 2019) - Lin, Qingwei; Fan, Mingjun; Jin, Ping; Riaz, Luqman; Wu, Zhenbin; He, Feng; Liu, Biyun; Ma, Jianmin
Abstract : Most aquatic vegetation restorations involve the transplantation of submerged macrophytes. Sediment type and the clonal size are of great significance as they determine the fate of submerged macrophytes. In order to ensure successful restoration, a simulation experiment was conducted using aquarium mesocosms to investigate the response of stolon propagation capacity, the morphological features and productivity of Vallisneria natans for four types of sediment (lake mud [L], lake mud + sand [L + S, 50:50, v/v mixture], sand [S], clay [C]), and three types of clonal sizes. Results showed that sediment types significantly affected V. natans biomass accumulation, stolon propagation ability, ramet morphological characteristics, and productivity, where the asexual reproduction ability and productivity ranked as L > L + S > S > C in four sediment types. Total biomass, maximum net production, number of ramets, root diameter, number of stolons, and stolon propagation rate were all highest in L. In L and L + S, the plant chlorophyll content was higher than in S and C. The root diameter and the ratio of aboveground/underground biomass in S were the smallest among the four sediments. Moreover, when more V. natans seedlings were linked, more ramets and biomass were produced. The stolon propagation rate was ranked as the stolon with single seedling greater than the stolon with two‐linked seedlings greater than the stolon with three‐linked seedlings in L and L + S. The concentration of total nitrogen, total phosphorus, and NO3 − ‐N in water was remarkably reduced in four aquariums. Findings provide a scientific basis for restoring submerged macrophytes in different sediment settings.